EFFECT OF WALKING EXERCISE ON URIC ACID LEVELS AMONG ELDERLY: A QUASI-EXPERIMENTAL STUDY - Karisma Dwi Ana; Yusiana Vidhiastutik; Fakhrun Nisa’ Fiddaroini (LPPM STIKES HUSADA JOMBANG, 2026)
Background: Hyperuricemia is a common health problem among the elderly and may reduce quality of life. One non-pharmacological intervention that can be applied is walking exercise. Objectives: This study aimed to determine the effect of walking therapy on reducing uric acid levels among elderly individuals at the Elderly Integrated Health Post (Posyandu Lansia) in Warungdowo Village, Pasuruan Regency. Methods: This study employed a quasi-experimental design with a one-group pretest–posttest approach. A total of 32 respondents were selected using total sampling technique. Uric acid levels were measured using a GCU (Glucose, Cholesterol, Uric Acid) meter. The intervention consisted of a walking exercise program conducted for several weeks, with a frequency of 3–5 times per week and a duration of 20–30 minutes per session. Data were analyzed using the Wilcoxon signed-rank test with a significance level of p < 0.05. Results: The results showed that the mean uric acid level decreased from 7.8 mg/dL before the intervention to 6.2 mg/dL after the intervention. Statistical analysis indicated a significant effect (p = 0.000 < 0.05). Conclusion: It can be concluded that walking therapy is effective as a non-pharmacological intervention in controlling uric acid levels among the elderly.